Effectiveness of Management of Absolute Return Funds In Poland During The COVID-19 Pandemic - Agnieszka MOSKAL (Communications of International Proceedings, 2021)
The aim of the article is to examine the effectiveness of management of absolute return funds in Poland in the period before and during the COVID-19 pandemic. The analysis used 23 absolute return funds operating in Poland in 2017-2021. The ability to generate alpha was used to assess the effectiveness of the management of the funds. As measures of effectiveness, risk-adjusted measures were used, such as: Jensen’s alpha, modified Jensen’s alpha and appraisal ratio. Absolute return funds, as alternative funds, should enable obtaining above-average rates of return regardless of the market situation. The obtained results indicate that absolute return funds in Poland during the COVID-19 pandemic obtained positive alpha values; however, fund managers were not able to generate higher rates of return than from market portfolios. An ineffective investment policy and legal changes on the Polish investment fund market resulted in a significant reduction in the value of assets under management of absolute return funds and a decrease in net cash flow in 2017-2019. On the other hand, the instability in the financial markets caused by the COVID-19 pandemic in 2020 resulted in an increased interest in investments in the absolute return funds market, which resulted in an increase in the value of assets and sales in 2020-2021.
Keywords: efficiency; COVID-19 pandemic; absolute return funds; management efficiency; Jensen's alpha